In Situ Assembly of MoSx Thin‐Film through Self‐Reduction on p‐Si for Drastic Enhancement of Photoelectrochemical Hydrogen Evolution. (6th October 2020) - Lin, Huiwen; Li, Sijie; Yang, Gaoliang; Zhang, Kai; Tang, Daiming; Su, Yu; Li, Yunxiang; Luo, Shunqin; Chang, Kun; Ye, Jinhua
Abstract: Strong coupling between the Si photocathode and a low‐cost cocatalyst is of great significance for enhancing the photoelectrochemical hydrogen evolution. Here, a facile method is proposed to in situ assemble amorphous MoS x (a‐MoS x ) thin‐film onto a single crystal p‐Si through a self‐reduction mechanism to achieve strong coupling. In the process of self‐reduction, the (MoS4 ) 2− anion is reduced to form a‐MoS x by the oxidation of H–Si to form SiO x, which is etched further to form H–Si again in the hydrofluoric aqueous solution. The cyclic formation of H–Si and SiO x plays a decisive role in the continuous deposition of a‐MoS x and provides a unique way to synthesize metal sulfides. Such a‐MoS x /p‐Si photocathode exhibits an excellent activity, achieving the optimal onset potential of +0.31 VRHE and the current density of −28.2 mA cm −2 at 0 VRHE with a Faradaic efficiency close to 98%, respectively, outperforming the thermally exfoliated 2H‐MoS2 and 1T‐MoS2 cocatalysts on p‐Si and comparable to the previous studies. The proposed method for uniform deposition at room temperature is simple to carry out and can be used for fabricating other Si‐based photoelectrodes. Abstract : A novel self‐reduction method is proposed to in situ assemble amorphous MoS x (a‐MoS x ) thin‐film onto planar p‐Si for efficient photoelectrochemical hydrogen evolution. The (MoS4 ) 2− anion is reduced to form a‐MoS x by the oxidation of H–Si to SiO x, which is etched further to form H–Si in the hydrofluoric aqueous solution. The cyclic formation of H–Si and SiO x promotes the continuous deposition of a‐MoS x .